Vibration characteristics of railway locomotive induced by gear tooth root crack fault under transient conditions. (January 2020) - Jiang, Jianzheng; Chen, Zaigang; Zhai, Wanming; Zhang, Tao; Li, Yifan
Highlights: A locomotive spatial dynamics model with gear tooth root crack is established. Responses of the model are obtained under transient condition and complicated excitations. Time-frequency analysis is used to reveal the fault vibration features. Angular synchronous average and statistical indicator are used in single processing. Results could supply some guidance for locomotive gear tooth fault diagnosis. Abstract: Dynamic interactions between wheel and rail are becoming more intensified under the development of locomotive towards high-speed, heavy-haul and high-power directions, which are more likely to cause failures in gear transmission system of high-power heavy-haul electric locomotive. The dynamic impact of the locomotive gear transmission system becomes more drastic, especially for the extreme operation conditions, such as traction/braking process. Gear fault diagnosis under unsteady conditions has always been a hot and difficult research spot, and revealing of the gear fault vibration characteristics under the transient conditions is the premise and basis for effective fault detection and diagnosis. In order to reveal the gear fault vibration characteristics of railway locomotive dynamics system, a spatial dynamic model of a heavy-haul electric locomotive considering the dynamic coupling effect of gear transmission system is proposed based on the multibody dynamics theory in this paper. Then the dynamic responses of the locomotive under transient condition are obtained by considering the complicated excitations induced by the wheel-rail nonlinear contact, gear mesh and tooth root crack. The time-frequency analysis and angular synchronous average method are adopted to investigate the fault vibration feature of the tooth root crack. Finally, the distribution and variation of vibration characteristics of the gear tooth root crack fault evolution are revealed by condition indicators such as the Crest Factor (CF), Kurtosis (K), Fourth Order Figure of Merit (FM4), M6A, and M8A. The results indicate that: (1) the time-frequency analysis results of vibration acceleration of wheelset and bogie frame and dynamic mesh force could reflect the fundamental mesh frequency and its harmonics, however, only the vertical and longitudinal vibration acceleration of the wheelset and the gear dynamic mesh force could reflect the fault vibration characteristics in time-frequency analysis results; (2) the FM4, M6A and M8A values of locomotive system vibration signal could effectively reflect the crack propagation on the dynamic features of the locomotive system after being processed by angular synchronous averaging method.